(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2025)
Monetary policy, a cornerstone of macroeconomic stabilization, employs various instruments to achieve objectives such as price stability, full employment, and sustainable economic growth. This article examines the principal tools utilized by central banks, categorizing them into traditional and unconventional approaches, and critically assesses their effectiveness. Traditional instruments, primarily open market operations, discount window facilities, and reserve requirements, operate by influencing short-term interest rates and the money supply through the banking system. The effectiveness of these tools hinges on robust market infrastructure and predictable economic agent behavior. In response to recent financial crises and persistent low inflation, central banks have increasingly deployed unconventional measures like quantitative easing, negative interest rates, and forward guidance. While these tools have demonstrated a capacity to provide liquidity and influence longer-term rates, their overall effectiveness is subject to diminishing returns, potential financial stability risks, and the prevailing economic context. The article also explores the intricate monetary policy transmission mechanism, the factors that enhance or constrain policy efficacy, and draws comparative insights from various economic regimes, concluding with a discussion of future challenges and policy implications.